The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.30525/2256-0742/2019-5-4-148-154
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptual Framework for the Operation of Financial Systems in the Context of Global Structural Transformations of Business Models of Banking

Abstract: The authors reveal fundamental tendencies of banks financial intermediation especially in the sphere of shadow banking and off-balance writes-off. Substantial transformations of financial system structure caused by liberalization of financial legislation, invention of brand new financial instruments and special risk-transferring schemes (special purpose entities via special investment vehicles) and the gradual process of banking universalization specifically the approximation of business models conducted by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…According to derived data following preliminary results of the research was obtained after application of mean average formula (1) as it is shown in table 3. It was 0 values for the category "V" for 2017 [11][12][13], 2018 [14][15][16][17][18] and 2019 [19][20][21][22] publishing years, but in only one case in 2020 [23] all categories had their respective values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to derived data following preliminary results of the research was obtained after application of mean average formula (1) as it is shown in table 3. It was 0 values for the category "V" for 2017 [11][12][13], 2018 [14][15][16][17][18] and 2019 [19][20][21][22] publishing years, but in only one case in 2020 [23] all categories had their respective values.…”
Section: Resultsmentioning
confidence: 99%
“…SHS Web of Conferences 92, 0 (2021) Globalization and its Socio-Economic Consequences 2020 In table 4 there is full representation of value per each of 20 inspected article. However, in order to better understand the tendency which is actually in line with main research question of the article, it was decided to make visualization of the data for the articles of 2010 [29], 2012 [30], 2015 [27], 2016 [28] and 2017 [11][12][13], 2018 [14][15][16][17][18], 2019 [19][20][21][22], 2020 [23][24][25][26] separately by using graphical tools of the Excel program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Financial systems are subject to transformations, which are the characteristic feature of the economic systems of many developed countries in the world [1]. Substantial transformations of the structure of the financial system are due to the liberalization of financial legislation, the invention of new financial instruments and the gradual universalization of banking activities [2].…”
mentioning
confidence: 99%